Hyperuricemia, use of antituberculosis drugs, and liver injury: case report - Vina Yuwantari; Nur Oktafiyani; Nurmelinda Hadi Ningrum; M. Hari Pristantiningtyas; Herya Putra Dharma; Muhammad Muchlis; Jainuri Erik Pratama; Fauna Herawati; Adji Prayitno Setiadi; Marisca Evalina Gondokesumo (Jurnal Teknologi Laboratorium)
Anti-tuberculous drug can cause idiosyncratic drug-induced liver injury (DILI). Considering the benefit risk, there will discontinuation therapy and rechallenge after symptom resolve. In addition to anti-tuberculosis drugs, liver injury can occur in patients with hyperuricemia. We report a 60-year-old male patient who had just used the initiation phase of OAT for 20 days experiencing hepatotoxic side effects characterized by complaints of nausea and vomiting for one week. Liver function examination results were normal with AST 23 u/L and ALT 9 u/L. OAT administration was temporarily stopped and started gradually with 150 mg rifampicin, 150 mg isoniazid and 500 mg ethambutol. The second day after using OAT again, given the full dose of 300 mg rifampicin, 300 mg isoniazid and 1000 mg ethambutol. The patient's condition improved after this modification of therapy so that therapy with three anti-TB drugs was continued until he was discharged from the hospital.